Estudio hematológico para determinación de Sarcocystiosis (Sarcocystis spp) en Camélidos Sudamericanos, faenados en el Camal Comunitario Yatzaputzan - Caicedo Paguay, Jonhatan Ricardo (2018)
A hematological study to determine sarcocystis (Sarcocystis spp.) In South American camelids was carried out at the Yatzaputzan Center for Animal Husbandry community, belonging to the Pilahuin Parish, Canton Ambato, December 17, which subjected 120 animals to the study Prior to slaughter taking into account physiological parameters, in addition the blood collection of the jugular vein of each animal was carried out, storage and the sending of samples to the laboratory to be analyzed versus its post mortem check, which is done once the animal is In this process the presence of the parasite is observed, inspecting different areas, in addition the inspection of organs was carried out and it was determined that usually the parasite will be found in the area of the animal neck and with respect to the organ in Where parasite this is in the liver, once this process is identified the case number that present this parasite, which expresses relevant results as its determination with regard to; Of the total of the samples, 27% was positive and 73% negative. In addition, the blood count included the evaluation of each of the variables, so I emphasize one of them, which is the Basophilic variable, which shows the Following units ranging from 0.11 to 0.18 x 10 (9) / L, whose value is increased and are outside the reference values that are 0.0-0.09 x 10 (9) / L, basophils are the variable that responds to this Research as these are the only values that have great relationship with positive animals in their post mortem verification.